2010
DOI: 10.5551/jat.4614
|View full text |Cite
|
Sign up to set email alerts
|

Current Therapy for Patients with Sitosterolemia –Effect of Ezetimibe on Plant Sterol Metabolism

Abstract: Sitosterolemia is a rare, autosomal recessive inherited sterol storage disease associated with high tissue and serum plant sterol concentrations, caused by mutations in the adenosine triphosphate-binding cassette (ABC) transporter ABCG5 or ABCG8 genes. Markedly increased serum concentration of plant sterols. such as sitosterol and campesterol, cause premature atherosclerosis and massive xanthomas. Hitherto known treatments for sitosterolemia, including a low-sterol diet, bile-salt binding resins, ileal bypass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 47 publications
(33 reference statements)
1
59
0
Order By: Relevance
“…The former mutation in the ABCG5 gene is one of the most common mutations among Asians with sitosterolemia 13) , while the latter mutation in the ABCG5 gene is considered novel. Meanwhile, both mutations in the MEFV gene identified in the proband are two of the most common mutations emia [17][18][19] . Careful monitoring and additional therapeutic approaches are needed to reduce her serum levels of sitosterol because of the unfavorable combination of hypersitosterolemia and systemic inflammatory disease, both of which have been shown to be associated with an increased risk of cardiovascular disease.…”
Section: Exome Sequencing and Bioinformatics Analysismentioning
confidence: 99%
“…The former mutation in the ABCG5 gene is one of the most common mutations among Asians with sitosterolemia 13) , while the latter mutation in the ABCG5 gene is considered novel. Meanwhile, both mutations in the MEFV gene identified in the proband are two of the most common mutations emia [17][18][19] . Careful monitoring and additional therapeutic approaches are needed to reduce her serum levels of sitosterol because of the unfavorable combination of hypersitosterolemia and systemic inflammatory disease, both of which have been shown to be associated with an increased risk of cardiovascular disease.…”
Section: Exome Sequencing and Bioinformatics Analysismentioning
confidence: 99%
“…However, the full clinical spectrum of sitosterolaemia is likely not known due to under-reporting and/or underdiagnosis of the condition in patients with mild or no clinical features, such as the affected sibling of the proband 3) . Whether these patients, particularly those with normal plasma LDL-C levels, should receive long-term treatment to reduce the plasma sterol levels at an early age remains uncertain, although it has been reported that patients with sitosterolaemia have developed coronary heart disease after the plasma LDL-C, but not sterol, level was treated and controlled 21) . It is worth noting that the mother of the proband and the two affected sisters each exhibited elevated HDL-C levels, particularly the mother, who had a markedly elevated HDL-C level of 3.0 mmol/L, a value compatible with the complete loss of the (cholesteryl ester transfer protein) CETP activity 22) .…”
Section: Discussionmentioning
confidence: 99%
“…Previous case reports have suggested that sitosterolaemia is associated with rapidly progressive atherosclerosis and premature coronary heart disease, and the administration of effective long-term therapy is advised in such cases in order to halt the progression of atherosclerotic disease 20,21) . In the general population, there are conflicting data as to whether mild to moderately elevated plasma plant sterol levels are a risk factor for cardiovascular disease 7) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In zebrafish, ApoA-I also contributes to sterol transporting system [18]. Excessive sterols are excreted out of the cells through the ATP-binding cassette sub-family G, member 5 and 8 (ABCG5 and ABCG8), back into the lumen in mammals [19]. Another ATP-binding cassette, sub-family A, member 1 (ABCA1), also exports sterols from the small intestinal epithelial cells into the circulation to contribute to the formation of HDL particles (Figure 1).…”
Section: Introductionmentioning
confidence: 99%